Writing Cover Letters That Address Instructor Feedback Improves Final Papers in a Research Methods Course. (January 2015) - Daniel, Frances; Gaze, Catherine M.; Braasch, Jason L. G.
We examined how writing cover letters to the instructor influenced final papers in research methods courses. After receiving instructor feedback on drafts of each section of an American Psychological Association style research paper throughout the semester, students in two classes wrote cover letters to the instructor explaining how the instructor feedback was incorporated into their final paper. Students in the two control classes received the same type of feedback throughout the semester but were not required to write cover letters. Students enrolled in the cover letter classes showed more improvement in the quality of their papers than the students in the control classes. Using cover letters to articulate how feedback is being incorporated may help students more efficiently organize and respond to instructor feedback. Future researchers might investigate whether students' reflective ability is a significant moderator in effective feedback utilization.